Models of disability : a brief overview - Letšosa, Rantoa; Retief, Marno (Hervormde teologiese studies, 2018)
Critical reflection on the importance of shaping disability-friendly – or disability-inclusive – congregations has enjoyed increasing attention in the field of practical theology in recent years. Moreover, the development of disability theology is a testament to the fact that practical theologians and the wider church community have taken serious notice of the realities and experiences of people with disabilities in our time. Nevertheless, even before the task of engaging in theological reflection from a disability perspective commences, it is necessary that theologians acquaint themselves with the various models of disability that shape people’s perceptions and ideas about people with disabilities. Guided by the principles of the interpretive task of practical theological investigation and cognizant of the importance of models of disability in shaping perceptions regarding people with disabilities, this article seeks to provide a brief overview of nine of the most dominant models of disability that are prevalent in our time. We shall utilise the typological approach to theoretical analysis in order to outline the basic characteristics of the various models.